Effect of macroprudential policies on sovereign bond markets: Evidence from the ASEAN-4 countries - Joshua Aizenman; Mohammed Gazi Salah Uddin; Tianqi Luo; Ranadeva Jayasekera; Donghyun Park (Asian Development Bank (ADB), 2023)
This paper examines whether prudential policies help to reduce sovereign bond vulnerability to global spillover risk in ASEAN-4 countries (Indonesia, Malaysia, the Philippines, and Thailand). We measure sovereign vulnerability within a risk connectedness network among sovereign bonds. The direct effect is that markets with tighter prudential policies have significantly smaller spillovers from the Treasury yield shocks of other regional and global economies. The sum of indirect and direct effects indicates that prudential policies reduce sovereign spillover risk in the long term. These findings suggest prudential policies have dual efficiency in sovereign risk regulation and Treasury internationalization.
Keywords: E52; E58; F42; 330; Sovereign bond; prudential policy; risk networks; connectedness; ASEAN